Valorization of Post-mining Dumping Grounds as Geotourism Sites on the Example of the Ruhr Region - Gawor, Łukasz; Szmatłoch, Anna; Dolnicki, Piotr (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
Post-mining dumping grounds are inseparably connected with the landscape of every largercity of the Ruhr Region and Upper Silesian Coal Basin. The restoration of these landforms belongs tothe most important elements of spatial planning in these areas. There are different methods of assigninga level of restoration and adapting the above mentioned landforms for functional purposes. The authorstried to evaluate dumping grounds in the Ruhr Region. In the paper, a method of valorization of dumping grounds is used, and an analysis using the conceptof valorization for dumping grounds from coal mining industry situated in Upper Silesian Coal Basinis done. This concept includes an evaluation based on two criteria: substantial value and accessibility.Twenty representative objects were analyzed according to their surface, location, land utilization andcomplexity of environmental problems.The obtained results allow rating the dumping grounds situated in the Ruhr Region highly, whichis connected with the high level of restoration. An attempt of valorization of post mining dumpinggrounds situated in the Ruhr Region using the rules of valorization elaborated in Upper Silesian CoalBasin showed that there were necessary some modifications in these rules. They were related mainly tothe way of using and location of the dumping grounds as well as general land utilization (e.g. in a touristicway). The analysis of the results of valorization shows the importance of effective restoration of thedumps, resulting from particular legal regulations. There is also one important fact that anthropogeniclandforms like post mining dumping grounds are used for didactic, recreation and landscape purposes.